Kepraktisan E-LKPD Berdiferensiasi Gaya Belajar pada Materi Pemanasan Global Fase E Sekolah Menengah Atas - Zikra, Ridha Hanifah; Dewi, Wahyuni Satria; Akmam, Akmam; Suherman, Dea Stivani (Indo-MathEdu Intellectuals Journal, 2025)
The Independent Curriculum is the latest curriculum in the world of Indonesian education which has been realized since 2021. The implementation of this independent curriculum demands learning that is tailored to the learning needs of diverse students, or called differentiated learning. The purpose of this study is to determine the level of practicality of E-LKPD with differentiated learning styles in the global warming material phase E of high school. This type of research is Development Research, a 4D development model with development steps, namely, define, design, develop, and disseminate. This research is part of the develop stage where the products made are applied in real life so that the level of practicality can be measured. The data analysis technique is descriptive analysis using descriptive statistics. Data was collected using a test sheet on the practicality of teacher responses and student responses on a Likert scale. The results of the study show that E-LKPD with differentiated learning styles in the global warming material phase E of high school has been practically used, with the average practicality score by teachers is 98.25% in the very practical category and the practicality score by students is obtained an average of 86.88% in the very practical category